Influence of shoe sole bending stiffness on sprinting performance - Nagahara, R.; Kanehisa, H.; Fukunaga, T. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: This study investigated the influence of shoe sole bending stiffness on sprint performance, in relation to anthropometric and strength-power capability characteristics of sprinters. METHODS: Seventeen male athletes performed three maximal effort 60-m sprints using spiked-shoes with different bending stiffness sole. Sprint times during 60-m sprint, anthropometry and strength-power capabilities represented by maximum toe-flexor test and rebound continuous ankle jump (AJ) of athletes were measured. RESULTS: The sprint times did not differ when shoe sole bending stiffness was altered by carbon fiber plates (CFPs) of 13.4 and 37.1 N/mm. The optimal bending stiffness for the fastest sprint was not associated with any anthropometric and strength-power variables. As results of stepwise-multiple-regression analyses, however, the left maximum toe-flexor strength (TFS) and contact time and jump height of rebound continuous AJ for a 0-30-m section with CFP of 13.4 N/mm, body mass for a 0-30-m section with CFP of 37.1 N/mm, and the left maximum TFS for a 30-60-m section with CFP of 37.1 N/mm were selected as predictors of changes in sprint times with stiffer sole shoes. CONCLUSIONS: These results indicate that, although sole bending stiffness of spiked-shoe may not affect the sprinting performance on average, changes in sprint time by the use of stiffer sole spiked-shoe for individuals will be predicted by toe-flexor strength, rebound continuous AJ performance, and body mass. The findings obtained here can be useful information for sprinters and coaches to choose the spiked shoe with an appropriate bending stiffness of sole for individuals